High spatial and temporal variability in Antarctic ice discharge linked to ice shelf buttressing and bed geometry - Miles, Bertie W. J.; Stokes, Chris R.; Jamieson, Stewart S. R.; Jordan, Jim; Gudmundsson, Hilmar; Jenkins, Adrian (Scientific Reports, 2022)
Antarctica’s contribution to global mean sea level rise has been driven by an increase in ice discharge into the oceans. The rate of change and the mechanisms that drive variability in ice discharge are therefore important to consider in the context of projected future warming. Here, we report observations of both decadal trends and inter-annual variability in ice discharge across the Antarctic Ice Sheet at a variety of spatial scales that range from large drainage basins to individual outlet glacier catchments. Overall, we find a 37 ± 11 Gt year−1 increase in discharge between 1999 and 2010, but a much smaller increase of 4 ± 8 Gt year−1 between 2010 and 2018. Furthermore, comparisons reveal that neighbouring outlet glaciers can behave synchronously, but others show opposing trends, despite their close proximity. We link this spatial and temporal variability to changes in ice shelf buttressing and the modulating effect of local glacier geometry.